PHILOSOPHICAL ASPECTS OF SUSTAINABLE DEVELOPMENT - Zadrożny, Paweł; Nicia, Paweł; Parzych, Piotr; Bajger, Romualda (GIS Odyssey Journal, 2021)
The history of mankind and the related history of the philosophy of nature demonstrate that, throughout centuries, people have always focused on the pursuit of understanding the world which they live in as well as the laws that govern it. The traditional philosophy concentrated on ontology and metaphysics, but with the development of civilisation as well as scientific and technical progress, it significantly expanded. The development of civilisation and its growing needs resulted in the increased anthropopressure on the natural environment, which caused significant changes. Civilisation and environmental threats, which mankind began to be aware of as late as in the last century, have also become the subject of considerations of contemporary philosophers. The pro-environmental and pro-ecological ideas that emerged in response to these threats often have their origins in philosophy. One of such ideas, which has now been firmly established legally, politically and socially, is the concept of sustainable development. Sustainable development for modern human is not only an idea, but it forms the basis of specific laws, policies and actions aimed at the survival of the human species. This paper presents examples of philosophical views on the idea of sustainable development – its origin, development, extent and perspectives.